Effect of control interventions for intestinal nematodiasis in areas with low prevalence in Changzhou City - Wang, Yun-Hua; Wang, Jian-Ming (Zhongguo xue xi chong bing fang zhi za zhi, 2013)
To evaluate the effect of control interventions for intestinal nematodiasis in areas with low prevalence, so as to explorethe effective measures for the control of intestinal nematode infections in Changzhou City, Jiangsu Province, China. The residents in Wujin, Jintan, Tianning districts were selected as monitor subjects and the infections of intestinal nematodes were investigated with Kato-Katz technique or the transparent tape anal swab method. The results were analyzed statistically and the cost-effectiveness was also analyzed. A total of 26 966 people were investigated and the total infection rate of intestinal nematodes was 0.37% (99/26 966). The infection rates of the local residents and floating population were 0.31% (63/20 267) and 0.55% (37/6 699), respectively, and the former was lower the latter (P < 0.01); the infection rates of urban residents and rural residents were 0.29% (44/15 328) and 0.47% (55/11 638),respectively, and the former was lower than the latter (P < 0.05). The 3 jurisdictions us